TINJAUAN HOLISTIK TARI TOPENG CEPAK KARYA CAHWATI SUGIARTO DI KABUPATEN TEGAL - Utami, Anne Amalia; Sulastuti, Katarina Indah (Greget : Jurnal Kreativitas dan Studi Tari, 2024)
The “Topeng Cepak” dance creation by Cahwati Sugiarto inspired of the Puppet “Golek Cepak” and “Topeng Endel” dance. Tradition art with little interest. However, Cahwati Sugiarto created the Topeng Cepak dance to people’s interest traditional art in Tegal Distrik. Research problem is (1) What is Cahwati Sugiarto role as an artist in Tegal District? (2) What is the form of the dance “Topeng Cepak” by Cahwati Sugiarto? (3) How does the public responds to the dance “Topeng Cepak” by Cahwati. Researchers use a holistic approach from H.B. Sutopo with three interrelated components such as Genetic Analysis, Objective Analysis, and Afective Analysis. The Researcher used the theory of dance form by Widyastutieningrum is physical form and expressions form. The Research used the theory of audience responses by Sulastuti is audience comprehender, audience trained, and audience general. This type of research is qualitative research with descriptive analysis method. Data Collection techniques using observation, interview, and literature review. The research results show that Cahwati Sugiarto is a talented and creative artist in creating works of art. The “Topeng Cepak” dance has a feminine and masuculine characteristics in perform. The “Topeng Cepak” dance is a single dance that has a movement style inspired by puppet “Golek Cepak”, “Topeng Tegalan” dance, Cirebon Style, Surakarta Style and Banyumasan Style. The “Topeng Cepak” dance get a good response from public, because it was unique, energetic, and music style from Cirebon and Banyumas.